2010
DOI: 10.1111/j.1524-4741.2010.00942.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Sentinel Node Biopsy for Breast Cancer Using Blue Dye Alone

Abstract: Blue dye alone (BDA), lymphoscintigraphy alone, or, a combination of the two techniques are used for sentinel node biopsy (SNB) in breast cancer. This study reviews the effectiveness of the SNB technique using BDA by measuring the node identification rate and comparing the cohort node positivity with expected rates from established nomograms. A consecutive case series was examined from the database. This included the learning experience of six surgeons. Patients with unifocal tumors estimated at less than 31 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…This finding is consistent with the consensus statement from the College of American Pathologists that does not recommend using IHC in the evaluation of SLNs. 2 Although results from the ACOSOG Z0010 trial are compelling and suggest that routine use of IHC in SLN evaluation is unnecessary, we would highlight one finding from the current article that is consistent with data previously published from our institution, 3 namely a relationship between invasive lobular histology and a higher incidence of positive SLNs on IHC staining. Invasive lobular tumors have a different architecture and more often have …”
Section: Jochelson MDsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding is consistent with the consensus statement from the College of American Pathologists that does not recommend using IHC in the evaluation of SLNs. 2 Although results from the ACOSOG Z0010 trial are compelling and suggest that routine use of IHC in SLN evaluation is unnecessary, we would highlight one finding from the current article that is consistent with data previously published from our institution, 3 namely a relationship between invasive lobular histology and a higher incidence of positive SLNs on IHC staining. Invasive lobular tumors have a different architecture and more often have …”
Section: Jochelson MDsupporting
confidence: 88%
“…However, the literature is replete with articles showing detection rates of less than 90%. [1][2][3][4] While the authors report a detection rate of 97.3%, they quote Lerman and colleagues 5 who believed that this hybrid methodology was more accurate (particularly in overweight patients) but reported a detection rate of only 90%. Another potentially confounding variable is the different technetium chelates used in reported results of SN biopsy.…”
Section: Referencesmentioning
confidence: 86%
“…Finally results from the ALMANAC study show that although the identification rate of the combined method was superior to BD alone (85.6% vs. 96%), there was no significant difference between the two techniques in identifying the positive nodes [10]. In contrast to these studies, other investigators do not find any evidence of higher identification rate of the combined technique versus blue dye alone [16,17] or radioisotope alone [18].…”
Section: Discussionmentioning
confidence: 70%
“…However, with improvements in radioisotope imaging and shielding, greater familiarity with the technique and absence of serious allergic reactions typical of those seen with blue dyes, many authors began to advocate the sole use of radiocolloids. Initial studies reported that blue dye alone performed poorly without the concomitant use of radiocolloids, but results comparable with dual‐modality SLN biopsy have been documented more recently. Serious allergic reactions were reported to be rare.…”
Section: Introductionmentioning
confidence: 99%